H⁺-activated Na⁺ influx in the ventricular myocyte couples Ca²⁺-signalling to intracellular pH. - Garciarena, C; Youm, J; Swietach, P; Vaughan-Jones, R (2013)
Acid extrusion on Na(+)-coupled pH-regulatory proteins (pH-transporters), Na(+)/H(+) exchange (NHE1) and Na(+)-HCO3(-) co-transport (NBC), drives Na(+) influx into the ventricular myocyte. This H(+)-activated Na(+)-influx is acutely up-regulated at pHi<7.2, greatly exceeding Na(+)-efflux on the Na(+)/K(+) ATPase. It is spatially heterogeneous, due to the co-localisation of NHE1 protein (the dominant pH-transporter) with gap-junctions at intercalated discs. Overall Na(+)-influx via NBC is considerably lower, but much is co-localised with L-type Ca(2+)-channels in transverse-tubules. Through a functional coupling with Na(+)/Ca(2+) exchange (NCX), H(+)-activated Na(+)-influx increases sarcoplasmic-reticular Ca(2+)-loading and release during intracellular acidosis. This raises Ca(2+)-transient amplitude, rescuing it from direct H(+)-inhibition. Functional coupling is biochemically regulated and linked to membrane receptors, through effects on NHE1 and NBC. It requires adequate cytoplasmic Na(+)-mobility, as NHE1 and NCX are spatially separated (up to 60μm). The relevant functional NCX activity must be close to dyads, as it exerts no effect on bulk diastolic Ca(2+). H(+)-activated Na(+)-influx is up-regulated during ischaemia-reperfusion and some forms of maladaptive hypertrophy and heart failure. It is thus an attractive system for therapeutic manipulation. This article is part of a Special Issue entitled "Na(+) Regulation in Cardiac Myocytes".